Intervention program the cutting: healing souls - Belletich Sandoval, Janis (2019)
This article proposes an intervention program and describes the addressing of the students who practice“Cutting”, what the parents’ roles and participation are and how this influences in its prevention. Furthermore,it includes activities that strengthen the skills, qualities and abilities in affected and non-affected students thatinvolve different subjects at school.